A comparative analysis on the compensation structure of an english medium school in Bangladesh (Based on Maple Leaf International School) - Zewar, Urfa (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2014.